Desoneraç\~oes do imposto sobre produtos industrializados e seus impactos sobre o mercado de trabalho - Igor Vinícius de Souza Geracy; Carlos Henrique Leite Corseuil; Fernando Gaiger da Silveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– Brazil federal tax policy changed course since 2007, when it was heavily activated to stimulate economic activity in a broad sense including job creation. A key policy instrument in this period was a tax on manufacturing products known as IPI (Imposto sobre produtos industrializados), whose tax rates decrease for a long list of products. Our main objective in this paper is to evaluate the impact of IPI reductions from 2007 to 2012 on labor market related outcomes, such as employment, hiring, separations and wages. We got null estimates for the impact in all labor market related variables for the whole period. Once we consider two subperiods, there appears impacts of reductions in IPI driving reductions in separations only for the 2010-2012 period. All these results are robust to alternative methodological procedures.
Keywords: J23; H25; 330; IPI; labor market